Glottic Keratosis: Significance and Identification of Laryngoscopic Findings - Mursalin M. Anis MD, PhD; Jennylee Diaz MS, CCC-SLP; Mausam Patel; Adam T. Lloyd SLP-D, CCC-SLP, MM; David E. Rosow MD (OTO Open, 2021)
Objective Glottic keratosis poses a challenge because a decision to biopsy must weigh the likelihood of dysplasia and cancer against the voice outcome after biopsy. We determined the significance of laryngoscopic findings and agreement among clinicians to identify those specific findings. Study Design Retrospective case-control study. Setting Tertiary care university hospital. Methods Adults with glottic keratosis with preoperative office laryngoscopies were included. Preoperative videostroboscopies were reviewed by a blinded reviewer. Multivariable logistic regression was used to examine the correlation between laryngoscopic appearance of glottic keratosis and presence or absence of high-grade dysplasia or carcinoma on biopsies. Consensus among head and neck cancer surgeons to detect specific laryngoscopic findings was evaluated by presenting representative laryngoscopies to a blinded cohort. Interrater reliability was calculated using Fleiss’s κ. Results Sixty glottic keratotic lesions met inclusion criteria. On logistic regression, both erythroplakia and aberrant microvasculature like vascular speckling were significantly associated with high-grade dysplasia and carcinoma, P = .002 and P = .03, respectively. Interrater reliability among clinicians to identify erythroplakia and aberrant microvasculature was minimal, κ = 0.35 and κ = 0.29, respectively. Interrater reliability was improved with the use of virtual chromoendoscopy. Conclusion The presence of erythroplakia and aberrant microvasculature in glottic keratosis is associated with the presence of high-grade dysplasia or carcinoma. Virtual chromoendoscopy can be used to improve reliability for detecting erythroplakia and vascular speckling, and this is a potential area for practice-based learning. Clinicians should identify and consider immediate diagnostic biopsy of suspicious glottic keratosis.